Nghiên cứu tối ưu hóa phản ứng tạo dẫn chất Dansyl trong định lượng S-allyl-L-Cystein trong Tỏi đen / Trần Hùng Sơn, Đỗ Hữu Xuân, Nguyễn Văn Bạch, Cao Văn Ánh, Hoàng Mỹ Hạnh, Nguyễn Thị Thanh Phương, Đào Văn Đôn - Trần, Hùng Sơn
S-Allyl-L-cysteine (SAC), as one of the most important bioactive compounds in black garlic was determinted by HPLC–FLD based on the derivatization with dansyl chloride (DnS). The dansyl derivatization were examined and finally optimized as: Temperature - 60 oC, the reaction time - 60 minutes, the pH of the buffer solution - 9.0 and the DnS concentration - 10mM. The proposed method proved applicable to determination of SAC in black garlic and to be a valuable contribution to quality control of black garlic products.